When Do Strong Parties “Throw the Bums Out”? Competition and Accountability in South African Candidate Nominations - Evan Lieberman; Philip Martin; Nina McMurry (Studies in Comparative International Development, 2021)
Existing accounts of centralized candidate selection argue that party elites tend to ignore constituent preferences in favor of internal party concerns, leading to accountability deficits. Yet this claim has been largely assumed rather than demonstrated. We provide the first detailed empirical analysis of the relationship between constituent opinion and candidate nominations in the absence of party primaries. We study contemporary South Africa, where conventional wisdom suggests that parties select candidates primarily on the basis of party loyalty. Analyzing more than 8000 local government councillor careers linked with public opinion data, we find that citizen approval predicts incumbent renomination and promotion in minimally competitive constituencies, and that this relationship becomes more pronounced with increasing levels of competition. By contrast, improvements in service provision do not predict career advancement. Under threat of electoral losses, South Africa's centralized parties strategically remove unpopular incumbents to demonstrate responsiveness to constituent views. However, party-led accountability may not improve development.
Keywords: 320; South Africa; accountability; candidate selection; public opinion; development